(untitled) (Eurasian Research Bulletin, 2024)
The emergence of the category of services, the emergence of various economic interests of the population in the economic system requires that the service sector function as a particularly important system. The functioning of such an economic system ensures the creation of enterprises that implement it. These types of enterprises have their own characteristics depending on the characteristics of the services. Such enterprises, like other types of enterprises, are profit-oriented, and their activities are taxed in the prescribed manner. The process of taxation of enterprises in the service sector has its own characteristics, and in this article these cases will be highlighted.